2019
DOI: 10.1002/isaf.1459
|View full text |Cite
|
Sign up to set email alerts
|

Stock price prediction using DEEP learning algorithm and its comparison with machine learning algorithms

Abstract: Summary Security indices are the main tools for evaluation of the status of financial markets. Moreover, a main part of the economy of any country is constituted of investment in stock markets. Therefore, investors could maximize the return of investment if it becomes possible to predict the future trend of stock market with appropriate methods. The nonlinearity and nonstationarity of financial series make their prediction complicated. This study seeks to evaluate the prediction power of machine‐learning model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 47 publications
(55 reference statements)
0
85
0
1
Order By: Relevance
“…and 2) practical: investment strategies [9], portfolio management [36], and beyond finance [29,72,78]. Financial models have previously relied only on numerical features [56,68] such as macroeconomic indicators [37]. This includes discrete (GARCH [11], rolling regression [71]), continuous (Markov chain [40] & stochastic volatility [2]), and neural approaches [48,55,58,68].…”
Section: Related Work 21 Multimodality In Financial Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…and 2) practical: investment strategies [9], portfolio management [36], and beyond finance [29,72,78]. Financial models have previously relied only on numerical features [56,68] such as macroeconomic indicators [37]. This includes discrete (GARCH [11], rolling regression [71]), continuous (Markov chain [40] & stochastic volatility [2]), and neural approaches [48,55,58,68].…”
Section: Related Work 21 Multimodality In Financial Forecastingmentioning
confidence: 99%
“…Financial models have previously relied only on numerical features [56,68] such as macroeconomic indicators [37]. This includes discrete (GARCH [11], rolling regression [71]), continuous (Markov chain [40] & stochastic volatility [2]), and neural approaches [48,55,58,68]. Contemporary approaches: Newer work categorized under Fundamental Analysis [1] based on the Efficient Market Hypothesis [60] highlight the success of multimodal data in finance [53], as they capture a wider set of affecting knowledge and their interdependencies.…”
Section: Related Work 21 Multimodality In Financial Forecastingmentioning
confidence: 99%
“…Many researchers have focused their efforts on applying these new techniques on financial markets (Dixon, Halperin, & Bilokon, 2020;El-Bannany et al, 2020;Galeshchuk & Mukherjee, 2017;Hatefi Ghahfarrokhi & Shamsfard, 2020;Nikou, Mansourfar, & Bagherzadeh, 2019;Sarlin & Marghescu, 2011;Sreedharan et al, 2020a;2020b). Hatefi Ghahfarrokhi and Shamsfard (2020) investigated the impact of social media data in predicting the Tehran Stock Exchange variables.…”
Section: Common Statistical and ML Techniques: An Overviewmentioning
confidence: 99%
“…However, LSTM has been used to predict the volatility of the S&P 500 (Xiong, Nichols, & Shen, 2015) and to forecast foreign exchange rates (Giles, Lawrence, & Tsoi, 2001). Nikou, Mansourfar, and Bagherzadeh (2019) predicted the daily close price data of a UK exchange-traded fund from January 2015 to June 2018 using four models of machine learning and indicated that the deep-learning method was better in prediction than the other methods. A hybrid forecasting system with evolutionary optimization and adaptive filtering was developed by Lahmiri (2020) to predict the price changes of S&P 500 data.…”
Section: Deep-learning Modelsmentioning
confidence: 99%